PENGGUNAAN MODEL DISCOVERY LEARNING DALAM MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA PADA PELAJARAN IPAS KELAS IVA SDN 34 PONTIANAK KOTA - Dian Febriani; Kartono; Mamik Untaria (STKIP Subang, 2023)
This research highlights the problem of limited critical thinking capacity of elementary school children in science and social science disciplines (IPAS). The aim of this project is to use a discovery learning model to improve students' critical thinking skills in Natural and Social Sciences. This research approach uses a lesson study model which consists of three cycles, namely Plan (planning), Do (doing or implementing), and See (observing and reflecting on the learning process). The research subjects were 32 Class IV A students of SDN 34 Pontianak City. Utilize assessments, observation notes, documentation, and collect data on critical thinking. According to research findings, students' overall critical thinking test scores reached 59% in cycle 1, 75% completeness in cycle 2 and 91% completeness in cycle 3. From the results of the tests carried out, there was an increase in students' critical thinking abilities in Science lessons. Nature and Social (IPAS) class IVA SDN 34 Pontianak City.